Analisis Ayat Jihad pada Fatwa MUI: Analysis of the Jihad Verse in the MUI Fatwa - Nur Ihsan Muhammad Idris (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to examine the verses of jihad in the MUI fatwa, thereby enriching the Islamic intellectual and literary heritage in the field of Quranic Tafsir. This research employs the library research method. The findings reveal that the verses mentioned in the fatwa correlate with the main ideas in the MUI fatwa on jihad, asserting that jihad is a core teaching in Islam to exalt the word of Allah. In peaceful situations, the implementation of jihad in the context of national life involves earnest and sustained efforts to uphold and elevate the religion of Allah through various good deeds. In contrast, in wartime, jihad means the obligation for Muslims to take up arms to defend the sovereignty of the country. The modern era's peaceful implementation of jihad involves earnest and sustained efforts to uphold and elevate the religion of Allah (li i’lai kalimat Allah) through various good deeds. These good deeds encompass fields such as preaching, education, technology, health, and social welfare. In wartime, jihad involves combating armed actions such as terrorism under the guise of jihad, armed drug trafficking, or separatist movements that seek to rebel against the legitimate government. All jihad movements are carried out by the legitimate government and not by individuals.